Mapping the research publication trends among ICAR-Animal Sciences Research Institutes in India: Web of Science-based scientometric study - KRISHNAN, P; HEMALATHA, M; AGARWAL, SUREKHA; GIREESH-BABU, P; NAVEENA, B M; RAO, CH SRINIVASA (The Indian Journal of Animal Sciences, 2023)
In the current study we have undertaken the scientometric analysis to map research publications from 19 different animal science research institutions under the Indian Council of Agricultural Research (ICAR), for a period of two decades (1998 to 2020), using the Web of Science (WoS) platform of Clarivate Analytics. We analyzed different scientometric parameters like year-wise citation records, institute-wise publication output, authorship pattern, publication types, top collaborating countries, research areas and journals, and relative growth rate and doubling time. Current analysis revealed that the maximum number of research articles were published in 2017 and ICAR-Indian Veterinary Research Institute contributed to the highest number of research papers and citations during thestudy period. Multi-authorship papers were significantly higher than single and double-authored papers. The study showed that in the field of animal sciences, the USA is the top collaborator with India resulting in 417 collaborative research papers. The Indian Journal of Animal Sciences carried the maximum number of research papers published by researchers from ICAR-Animal Science Research Institutes (ASRI) during 1998-2020. Relative Growth Rate (RGR) showed a decreasing trend in research publications while the doubling time increased during this period. The paper provides a comprehensive account of the research trends in animal sciences research and also insights for strengthening research focus in India.